Risks and Challenges of Oversized Transport in the Energy Industry - Dariusz Masłowski; Małgorzata Dendera-Gruszka; Julia Giera; Ewa Kulińska; Krzysztof Olejnik; Justyna Szumidłowska (Energies)
The transport of oversized loads, such as wind turbine components, represents a key logistical challenge due to specific technical and regulatory requirements. The development of the renewable energy sector, particularly wind energy in Poland, has significantly increased the demand for this type of transport. The implementation of wind farm construction projects requires not only advanced technological solutions but also special attention to transport safety and the organization of logistical processes. This study employed the FMEA (Failure Mode and Effects Analysis) risk analysis method, which allows for the identification of potential defects and their causes. Data were collected through surveys, interviews with representatives of transport companies, and field observations. The research sample included 11 companies specializing in oversized transport in Poland and European countries. Based on the gathered information, 15 typical risks associated with the transport of wind turbine components were identified. The most significant risks include the possibility of road accidents and discrepancies between the actual dimensions of the cargo and the transport documentation. The results highlight the need for improvements in route planning, precise verification of cargo parameters, and better management of administrative processes related to obtaining permits. The development of the wind energy sector and dynamic investments in wind farms make the optimization of oversized transport a crucial element in supporting the execution of eco-friendly projects and sustainable development.